Antimicrobial Activity of Psidium Guajava Leaves Extract Against Foodborne Pathogens - Azizan, Nurul Alia; Wahab, Noor Zarina Abd; Mohamad, Noor Ayunie; Shambely, Azlin Sham; Othman, Ahmad Syibli (International Journal of Psychosocial Rehabilitation, 2020)
Foodborne disease has been associated with microorganisms like bacteria. This study was designed to evaluate the methanolic extracts of Psidium guajava leaves for antibacterial activity properties. The antibacterial activities of the extract were studied against four different bacteria causing foodborne infection; Staphylococcus aureus, Bacillus cereus, Escherichia coli and Salmonella typhimurium using disc diffusion method. The methanol extracts of P. guajava leaves were active against the Gram-positive bacteria S. aureus and B. cereus with minimal inhibitory concentration (MIC) of 30 mg/ml. However, the extract was inactive against the Gram-negative bacteria • coli and S. typhimurium although 1000 mg/ml concentration was used. Thus, our results suggest that P. guajava leaves extract contain antimicrobial compound that could be used to treat Gram positive bacterial infections that cause foodborne infection. Furthermore, this study supports its sustainability of medicinal use in the treatment of foodborne infections in worldwide.